Solid-state lithium metal battery composite polymer electrolyte, preparation method and application thereof and all-solid-state battery
By combining PEO, PVDF-HFP, and LLZO and optimizing the preparation process, the problems of high crystallinity, low conductivity, and insufficient mechanical strength of polymer electrolytes were solved, and a high-performance composite electrolyte membrane suitable for all-solid-state lithium batteries was prepared.
Patent Information
- Application Number
- CN202512038140.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-03-20
AI Technical Summary
Existing polymer electrolytes have high crystallinity at room temperature, low ionic conductivity, and insufficient mechanical strength. Furthermore, they are prone to forming bubbles and pores during the preparation process, which affects battery performance.
A dense composite electrolyte membrane is formed by combining PEO, PVDF-HFP and LLZO with a specific mass ratio and preparation process, including slow solidification, static defoaming, staged drying and vacuum solvent removal.
It improves room temperature ionic conductivity, enhances mechanical strength and flexibility, inhibits lithium dendrite growth, and improves the cycle stability and rate performance of all-solid-state lithium batteries, making it suitable for high-voltage cathode materials.
Smart Images

Figure CN121709704A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of all-solid-state lithium battery electrolyte technology, specifically relating to a solid-state lithium metal battery composite polymer electrolyte, its preparation method, application, and all-solid-state battery. Background Technology
[0002] With the development of new energy vehicles, energy storage systems, and high-energy-density consumer electronics, lithium-ion batteries suffer from problems such as rapid capacity degradation, low safety, and limited cycle life. Lithium metal has become a focal point due to its high theoretical specific capacity (3860 mAh g⁻¹) and low redox potential (-3.040 V relative to the standard hydrogen electrode). Meanwhile, solid-state polymer electrolytes offer significant advantages over traditional organic liquid electrolytes in terms of energy density, safety, and high voltage adaptability. Among these, polymer-based solid-state electrolytes have become an important research direction for all-solid-state lithium batteries due to their good flexibility and interfacial compatibility. Polyethylene oxide (PEO) is the most commonly used polymer matrix, and its molecular chains contain a large number of ether oxygen groups, which can coordinate with lithium ions and provide ion conduction channels. However, PEO has high crystallinity at room temperature, restricting chain segment movement and resulting in insufficient room-temperature ionic conductivity (ionic conductivity of 10). -6 -10 -8 S cm -1 Furthermore, polarization is prone to occur during cycling, which limits the rate performance and low-temperature applications of the battery.
[0003] Polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) possesses excellent mechanical strength and a high dielectric constant, which facilitates lithium salt dissociation and improves the stability and dendrite resistance of the electrolyte membrane. However, when used alone, PVDF-HFP exhibits poor ionic conductivity, making it difficult to meet the energy density requirements of batteries. Combining PEO with PVDF-HFP can reduce the crystallinity of PEO to some extent, while maintaining both flexibility and mechanical strength. However, the two compounds have significant differences in physicochemical properties, and variations in compatibility, phase distribution, and microstructure at different ratios can significantly affect ion conduction pathways; therefore, further optimization of the compounding ratio is necessary.
[0004] In existing technologies, researchers often add oxide-based inorganic fillers, such as LLZO (Li7La3Zr2O). 12 LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), LLZTO (Li 6.4 La3Zr 1.4 Ta 0.6 O 12Not only can it serve as an inorganic framework to enhance the mechanical properties of membranes, but it can also promote lithium salt dissociation and increase carrier concentration through Lewis acid-base interactions between surface polar groups and lithium salts. At the same time, it can inhibit polymer crystallization, enhance chain segment movement, and increase ion migration rate, thereby significantly improving the ionic conductivity of composite electrolytes. For example, numerous literature reports that LLZO nanoparticles, sheet-like or cubic particles can significantly improve the room temperature ionic conductivity of PEO-based solid electrolytes by 1–2 orders of magnitude.
[0005] In the preparation of solid-state electrolytes, the solvent evaporation rate and the membrane formation environment have a significant impact on the final microstructure. DMF, as a high-boiling-point, highly polar solvent, can effectively dissolve PVDF-HFP and participate in the formation of a homogeneous sol system. However, DMF evaporates slowly, and improper handling during the membrane formation stage can easily lead to bubbles, voids, or phase separation, thereby reducing the electrolyte's conductivity and mechanical strength. Therefore, it is necessary to rationally design the settling, demolding, drying, and vacuuming steps to ensure the formation of a uniform and dense microstructure in the composite solid-state electrolyte. Summary of the Invention
[0006] To address the shortcomings of existing technologies and overcome the deficiencies of current polymer electrolytes, particularly those based on polyethylene oxide (PEO) which suffer from high crystallinity, low ionic conductivity, severe polarization, and insufficient mechanical strength at room temperature, this invention provides a solid-state lithium metal battery composite polymer electrolyte, its preparation method, applications, and an all-solid-state battery. This invention effectively improves the ionic conductivity and interfacial stability of the electrolyte, while balancing flexibility and mechanical strength.
[0007] The technical solution provided by this invention is as follows: A method for preparing a solid-state lithium metal battery composite polymer electrolyte includes the following steps: mixing polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), polyethylene oxide (PEO) and LLZO with a solvent to obtain a sol, then spreading the sol into a film, drying it under static conditions to remove the solvent, and obtaining the solid-state lithium metal battery composite polymer electrolyte.
[0008] The above technical solution, through the compounding of PEO, PVDF-HFP and LLZO in a specific mass ratio, can construct a synergistic structure that balances flexibility, strength and conductivity, thereby improving the room temperature ionic conductivity of the composite electrolyte, suppressing lithium dendrite growth, and enhancing the cycle stability and rate performance of all-solid-state lithium batteries.
[0009] Preferably, the mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene copolymer is 5:5-9:1.
[0010] Preferably, the amount of lithium bis(trifluoromethanesulfonyl)imide is 35-60% of the total mass of PEO and PVDF-HFP, preferably 36%.
[0011] Preferably, the amount of LLZO used is 5wt%-40wt% of the total mass of PEO and PVDF-HFP.
[0012] Preferably, the molecular weight of the polyethylene oxide is 500,000-1,000,000, more preferably 600,000; Preferably, the molecular weight of the polyvinylidene fluoride-hexafluoropropylene copolymer is 350,000-450,000, and more preferably 400,000.
[0013] Preferably, the solvent is N,N-dimethylformamide (DMF) or N-methylpyrrolidone, and the solid content of the solution is 5%-15%, preferably 8%.
[0014] Specifically: The sol is evenly poured onto the PTFE board and spread into a film. Then the PTFE board is placed in a desiccator to solidify slowly. Let the solidified sample stand at 40℃-50℃ for 2-4 hours; The obtained sample was then placed in a vacuum drying oven at 55℃-65℃ and vacuumed in a gradient manner at a vacuum level of -0.02MPa to -0.08MPa for 24-72 hours.
[0015] In the above technical solution: By slow solidification, the bubbles and defects generated during solvent evaporation are reduced, effectively improving the compactness of the solid electrolyte membrane and making it more suitable for lithium foil anode systems. By first allowing the film to stand to defoam, then pouring it onto the surface of a PTFE plate and placing it in a desiccator for slow coagulation, followed by drying with a forced air to remove some of the solvent, and finally vacuum drying the remaining solvent, the formation of bubbles and pores in the membrane is effectively suppressed, thereby improving the membrane's density and mechanical strength.
[0016] The present invention also provides a solid-state lithium metal battery composite polymer electrolyte, which is prepared by the aforementioned preparation method.
[0017] This invention also provides applications of composite polymer electrolytes for solid-state lithium metal batteries, as solid-state electrolyte materials or quasi-solid-state electrolyte materials. A quasi-solid-state electrolyte is a composite material with a solid polymer / inorganic material as a continuous framework or main body, wherein a considerable amount of liquid electrolyte is filled or impregnated, with the liquid electrolyte content accounting for 0%-5%.
[0018] The present invention also provides an all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane, and a negative electrode, wherein the solid electrolyte membrane is the solid lithium metal battery composite polymer electrolyte.
[0019] Specifically, the positive electrode is a lithium iron phosphate positive electrode, a ternary positive electrode, or a lithium-rich manganese positive electrode.
[0020] The present invention has the following beneficial effects: 1. Improve ionic conductivity: The introduction of PVDF-HFP effectively reduced the crystallinity of PEO, making PEO segments more mobile at room temperature, thereby improving the migration rate of lithium ions. Achieving 10 at 30℃ -5 -10 -4 S cm -1 The ionic conductivity is orders of magnitude higher than that of the pure PEO system. Moreover, the addition of LLZO not only provides an inorganic framework, but also promotes lithium salt dissociation through Lewis interactions between surface oxygen ions and LiTFSI, which can increase the ionic conductivity by 1-2 orders of magnitude.
[0021] 2. Enhance mechanical strength and flexibility: PVDF-HFP imparts high mechanical modulus and good film-forming properties to the electrolyte membrane, allowing it to remain intact during repeated bending, suppressing lithium dendrite penetration, and improving battery cycle life.
[0022] 3. Optimize interface stability: PVDF-HFP has a high dielectric constant, which helps the dissociation of LiTFSI. At the same time, the presence of F in PVDF-HFP enables the formation of an SEI or CEI layer when the polymer electrolyte and electrode are in contact, reducing the interfacial impedance between the electrolyte and the lithium metal anode, reducing polarization, suppressing the formation of lithium dendrites, and improving the rate performance of the battery.
[0023] 4. Controllable preparation process: The unique process of using a dryer for slow condensation, step drying, and vacuum removal of DMF results in a denser membrane structure, reduced pores and bubbles, and improved mechanical strength and electrochemical stability. Meanwhile, the overall preparation process is simple and highly reproducible.
[0024] 5. Wide applicability: The polymer solid electrolyte of this invention is not only applicable to lithium iron phosphate batteries, but also allows for LSV measurement by assembling SS / / LI asymmetric cells. The electrochemical window of the electrolyte membrane can reach 4.8V, and it can also be matched with high-voltage cathode material systems (such as ternary cathode materials and lithium-rich manganese-based cathode materials).
[0025] In summary, this invention overcomes the problems of high crystallinity, low conductivity, and insufficient mechanical properties of existing PEO electrolytes while taking into account both high ionic conductivity and excellent mechanical properties, and has significant application prospects. Attached Figure Description
[0026] Figure 1 This is a flowchart of the preparation method of the present invention.
[0027] Figure 2 This is a cross-sectional SEM image of the membrane from Example 1.
[0028] Figure 3 This is an optical image of the film in Example 1.
[0029] Figure 4 This is a 0.2C cycling graph of PEO:PVDF-HFP at different mass ratios at room temperature.
[0030] Figure 5 This is a graph showing the magnification test results of PEO:PVDF-HFP at different mass ratios.
[0031] Figure 6 This is a graph showing the film formation quality of Comparative Example 1.
[0032] Figure 7 This is a graph showing the film formation quality of Comparative Example 2.
[0033] Figure 8 This is a graph showing the film formation quality of Comparative Example 3. Detailed Implementation
[0034] The principles and features of the present invention are described below. The embodiments given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, the test methods used in the embodiments are conventional methods; the materials and reagents used are commercially available unless otherwise specified.
[0035] Polyvinylidene fluoride-hexafluoropropylene copolymers utilize existing technologies, such as those from the McLean brand.
[0036] Polyethylene oxide utilizes existing technologies, such as the Aladdin brand.
[0037] In one specific embodiment, the preparation method of the solid-state lithium metal battery composite polymer electrolyte includes the following steps: Pretreatment of lithium salts, PEO and PVDF-HFP: For each experiment, the reagents were first dried in a vacuum drying oven at 60°C for 24 hours (except for lithium salts, which are prone to absorbing water, and were directly stored in a glove box after the first drying treatment) to ensure that lithium salts and PEO were sufficiently dry.
[0038] Electrolyte preparation: First, weigh an appropriate amount of PVDF-HFP outside the glove box, calculate the required amounts of each reagent, and then accurately weigh lithium bis(trifluoromethanesulfonyl)imide lithium (LiTFSI) to ensure it is free from air and moisture contamination. Then, outside the glove box, add N,N-dimethylformamide (DMF) solvent and magnetically stir for 5 hours at 50°C to form a homogeneous polymer solution. Next, add the pre-dried amount of PEO and continue stirring overnight to ensure thorough mixing of the chain segments. After stirring stops, allow the solution to stand for 30 minutes to eliminate air bubbles. The mixed sol is then uniformly poured onto the surface of a polytetrafluoroethylene (PTFE) plate, allowing it to spread naturally to form a film. To suppress defects caused by rapid DMF evaporation, the film, along with the PTFE plate, is placed in a desiccator for slow solidification. It is then transferred to a forced-air drying oven where some solvent is slowly evaporated at different temperatures to prevent pore formation due to excessive solvent evaporation. Finally, the sample is placed in a 60°C vacuum drying oven and subjected to layered vacuum treatment for 48 hours to completely remove residual solvent. The resulting electrolyte membrane was punched into 19 mm diameter discs using a punching machine and quickly transferred back to the glove box to remove air-adsorbed moisture. Subsequently, lithium metal all-solid-state batteries were assembled and subjected to tests including cycle life, conductivity, and electrochemical stability window. The flowchart of the preparation method can be found in the following reference. Figure 1 .
[0039] Example 1 Material selection: Main polymer: Polyethylene oxide (PEO, molecular weight ≈ 600,000). Auxiliary polymer: polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight ≈400,000). Lithium salt: Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, battery grade); Inorganic filler: LLZO (commercial) Solvent: N,N-dimethylformamide (DMF, analytical grade).
[0040] Mixing ratio: The mass ratio of PEO to PVDF-HFP is 6:4. Preparation steps: 1. Outside the glove box, weigh a certain amount of PVDF-HFP into the reaction flask, and inside the glove box, weigh the required amount of LiTFSI to prevent it from absorbing moisture.
[0041] 2. Outside the glove box, add a predetermined amount of DMF (calculate the required amount of DMF solvent based on the total mass of solids in the solution, with a solid content of 8%, including PEO, PVDF-HFP, LiTFSI, and LLZO), and stir at 50°C for 5 hours to obtain a transparent solution.
[0042] 3. Add a certain amount of dried PEO to the above solution and continue stirring overnight to ensure uniform mixing.
[0043] 4. After stopping stirring, let the solution stand for 30 minutes to remove air bubbles.
[0044] 5. Pour the sol evenly onto the PTFE sheet and allow it to spread naturally into a film. Place the PTFE sheet in a desiccator to solidify slowly to prevent the formation of bubbles and pores.
[0045] 6. After the initial film formation, transfer the sample to a forced-air drying oven and let it stand at 40℃ and 50℃ for 3 hours each, without forced air to slowly evaporate part of the DMF.
[0046] 7. Then place the sample in a 60℃ vacuum drying oven and apply vacuum at -0.02MPa, -0.04MPa, -0.06MPa and -0.08MPa levels for 48 hours to completely remove residual solvent.
[0047] 8. Use a punching machine to cut electrolyte membrane sheets with a diameter of 19 mm, put them back in the glove box to dehydrate, and then assemble the lithium-ion full battery.
[0048] Example 2 Compared with Example 1, the mass ratio of PEO to PVDF-HFP in step (3) is changed to 9:1. Due to the low content of PVDF-HFP, it is difficult to form an effective flexible support network. The shrinkage and stress concentration of the membrane during the drying process are more significant, resulting in a decrease in film toughness. It was found that the mechanical properties of the membrane are very poor and the viscosity is high. Phenomena such as difficulty in completely peeling off the film, local tearing, and film adhesion occur on the mold.
[0049] Example 3 Compared with Example 1, this embodiment adds 5wt% LLZO of the total mass of PEO and PVDF-HFP to the required amount of LiTFSI in step (1) for inorganic doping modification. This significantly improves the mechanical strength and peelability of the film. The assembled battery performs excellently: the first-cycle discharge specific capacity reaches 158 mAh g. -1 At 0.2C, the energy retention rate is 93.6% after 80 cycles, and it remains stable at 115 mAh g at 0.5C. -1 The cycle performance is stable.
[0050] Example 4 Compared with Example 1, in this embodiment, when weighing the required amount of LiTFSI in step (1), 25 wt% of LLZO (total mass of PEO and PVDF-HFP) was added for inorganic doping modification. Obvious filler agglomeration was observed. Due to the excessive amount of LLZO added, its dispersibility in the polar solvent system was limited, and some particles were difficult to fully wet and appeared in an "undissolved" state, leading to a decrease in system uniformity. However, LSV testing revealed that the composite electrolyte could still stably withstand a high voltage of approximately 4.8 V and could tolerate lithium-rich manganese-based and ternary cathode materials. However, due to prominent interface contact issues, the discharge specific capacity of the assembled battery decreased.
[0051] Example 5 Compared with Example 1, this embodiment changes the amount of DMF in step (2) to make the solid content 15%. When the solid content is 15%, the viscosity increases, more bubbles are generated during stirring, the drying time in PTFE is longer, the prepared film is thicker, and the mechanical properties are enhanced. However, many cracks are observed on the film surface by SEM, which will lead to a decrease in electrical conductivity.
[0052] Comparative Example 1 Compared with Example 1, this embodiment reduces the static defoaming step (4). It was found that due to the uneven stirring speed, the solution is prone to carrying a large number of bubbles during the stirring process. During the stirring process, the solution is prone to generating bubbles. If it is directly poured into a mold, due to the large surface tension of the liquid, the bubbles are not easy to float and break and release, which easily forms residual holes, affecting the density and mechanical properties of the electrolyte membrane.
[0053] Comparative Example 2 Compared to Example 1, this embodiment also omits the slow drying in the blower drying oven in step (6). After the membrane cast on the PTFE plate is left to stand in the dryer, although the surface has solidified, a large amount of DMF still remains inside. When directly transferred to the vacuum drying oven under negative pressure, due to the uneven surface tension of the surface curing layer, the internal solvent vaporizes and forms bubbles that are difficult to break and expel. At the same time, under high temperature and negative pressure conditions, DMF evaporates rapidly, and the liquid accumulates and is difficult to expel, resulting in the solvent inside the membrane not being able to evaporate completely, thus affecting the density and uniformity of the membrane.
[0054] Comparative Example 3 Compared with Example 1, this embodiment changes the vacuum degree of the vacuum drying oven in step (7). In step seven, the vacuum degree is directly reduced to -0.08 MPa, and the membrane is dried for 48 hours to completely remove residual solvent. This method causes the solvent on the membrane surface and inside to vaporize instantly, easily forming pores on the membrane. Using staged vacuuming can gradually remove residual solvent and bubbles, avoiding defects on the membrane surface or inside, reducing local adhesion, and making it easier to separate the electrolyte membrane from the mold, thereby significantly improving the preparation success rate and membrane uniformity.
[0055] Comparative Example 4 Patent CN 117317394 A discloses a method for preparing a solid-state lithium-ion battery: a suspension is poured onto a PTFE film plane, the suspension is leveled with a scraper, and after standing in a glove box for 4 hours, it is transferred to a vacuum drying oven and vacuum dried at 80°C for 12 hours to remove the film and punch holes to obtain an electrolyte membrane.
[0056] Patent CN 118136944 A: discloses a method for preparing a PEO-based solid electrolyte without interface modification: pour the casting solution into a silicone mold, allow the acetonitrile solvent to evaporate naturally at room temperature for 12 hours to form a film, and then transfer it to a vacuum oven to dry at 60°C for 24 hours to completely remove the acetonitrile.
[0057] Patent CN 118610557 A discloses a method for preparing a solid-state battery composite electrolyte membrane material: the room temperature drying time is 6-10 h, the vacuum drying temperature is 60-120℃, and the drying time is 2-24 h.
[0058] Most existing patents only use room temperature and direct vacuum drying during the demolding process, lacking the preliminary treatment of forced air drying, which easily leads to residual air bubbles in the membrane and difficulty in demolding. Experiments show that the present invention effectively improves the membrane density and descalability through staged drying.
[0059] Comparative Example 5 Compared with Example 1, this embodiment does not add PVDF-HFP blending, but directly adds PEO, LITFSI and solvent DMF and stirs at 50°C for 5 hours to obtain a transparent solution. The subsequent steps are the same. The experiment shows that the single polymer PEO system has low room temperature ionic conductivity and insufficient mechanical strength of the film. During the peeling process, it will lead to the self-adhesion of the film and the film not having enough mechanical strength to peel off.
[0060] Comparative Example 6 Compared with Example 1, this embodiment changes the LiTFSI content in step one to 41% of the total mass of PEO and PVDF-HFP. Although the high salt concentration can increase the number of ion carriers, the coordination of excessive Li⁺ with TFSI⁻ will restrict the flexible movement of PEO chain segments, reduce the plasticizing effect of the polymer, and at the same time trigger undesirable interactions between the polymer and the salt, promote salt aggregation or crystal precipitation, resulting in phase separation and a decrease in mechanical properties, ultimately inhibiting the overall ion conduction performance.
[0061] like Figure 2 The image shown is a cross-sectional SEM image of the membrane from Example 1. As can be seen from the image, the membrane thickness is only about 60 μm, indicating that the electrolyte membrane prepared by this method is very thin.
[0062] like Figure 3The image shown is an optical diagram of the membrane of Example 1. The image shows that the membrane is very dense without pores and has good flexibility.
[0063] like Figure 4 The figure shows the 0.2C cycling curves of PEO:PVDF-HFP at different mass ratios (including Examples 1 and 2) at room temperature. This figure shows that the pure polymer electrolyte system prepared by mixing PEO and PVDF-HFP at a mass ratio of 6:4, when assembling a Li / / LFP full cell, maintains a stable specific capacity of 145 mAh g⁻¹ at 25°C during 0.2C cycling. -1 It has a retention rate of >92% after 200 cycles, a higher discharge specific capacity than other systems, and is more stable in cycling.
[0064] like Figure 5 The figure shows the rate test results for PEO:PVDF-HFP at different mass ratios (including Examples 1 and 2). It can be seen that at 0.5C and 1C, the discharge specific capacity for PEO:PVDF-HFP = 6:4 is 140 and 120 mAh g, respectively. -1 It is clearly superior to others.
[0065] like Figure 6 The figure shows the film quality of Comparative Example 1. As can be seen from the figure, the lack of static defoaming resulted in dense bubbles, making film peeling impossible.
[0066] like Figure 7 The figure shows the film quality of Comparative Example 2. As can be seen from the figure, Comparative Example 2 lacked a slow drying oven; instead, it was directly placed in a vacuum drying oven, resulting in a large number of bubbles still forming on the film surface.
[0067] like Figure 8 The figure shows the film quality of Comparative Example 3. As can be seen from the figure, in Comparative Example 3, the vacuum was directly reduced to -0.08 MPa, and the film had undergone preliminary drying. However, the excessive negative pressure still caused bubbles to form.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a solid-state lithium metal battery composite polymer electrolyte, characterized in that, Includes the following steps: Polyvinylidene fluoride-hexafluoropropylene copolymer, lithium bis(trifluoromethanesulfonyl)imide, polyethylene oxide and LLZO are mixed with a solvent to obtain a sol. The sol is then spread into a film and dried under static conditions to remove the solvent, thereby obtaining the solid lithium metal battery composite polymer electrolyte.
2. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to claim 1, characterized in that: The mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene copolymer is 5:5-9:
1.
3. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to claim 1, characterized in that: The amount of lithium bis(trifluoromethanesulfonyl)imide is 30-60% of the total mass of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer.
4. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to claim 3, characterized in that: The amount of LLZO used is 5wt%-40wt% of the total mass of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene copolymer.
5. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to claim 1, characterized in that: The average molecular weight of polyethylene oxide is 500,000 to 1,000,000; The average molecular weight of polyvinylidene fluoride-hexafluoropropylene copolymer is 350,000-450,000.
6. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to claim 1, characterized in that: The solvent is N,N-dimethylformamide or N-methylpyrrolidone, and the solid content of the solution is 5%-15%.
7. The method for preparing the solid-state lithium metal battery composite polymer electrolyte according to any one of claims 1 to 6, characterized in that: The specific steps for spreading the sol into a film and drying it under static conditions to remove the solvent are as follows: The sol is evenly poured onto the PTFE board, spread into a film, and then the PTFE board is placed in a desiccator to solidify slowly. Let the solidified sample stand at 40℃-50℃ for 2-4 hours; The obtained sample was then placed in a vacuum drying oven at 55℃-65℃ and vacuumed in a gradient manner at a vacuum level of -0.02MPa to -0.08MPa for 24-72 hours.
8. A solid-state lithium metal battery composite polymer electrolyte, characterized in that: It is prepared according to any one of claims 1 to 7.
9. An all-solid-state battery, comprising a positive electrode, a solid electrolyte membrane, and a negative electrode, characterized in that: The solid electrolyte membrane is the solid lithium metal battery composite polymer electrolyte as described in claim 8; the positive electrode is a lithium iron phosphate positive electrode, a ternary positive electrode, or a lithium-rich manganese positive electrode; and the negative electrode is a lithium sheet.
10. An application of the solid-state lithium metal battery composite polymer electrolyte according to claim 8, characterized in that: As a solid electrolyte material or a quasi-solid electrolyte material.
Citation Information
Patent Citations
Solid-state lithium ion battery and preparation method thereof
CN117317394A